Can you please solve this?!?
![Can you please solve this class=](https://us-static.z-dn.net/files/dc2/565cf66f4aabd2065bc1740d3ed316bf.jpg)
[tex]\bold{\huge{\blue{\underline{ Solution }}}}[/tex]
Here, We have,
[tex]\sf{√(a-b-c)(b-c-d)=√ab-√bc-√cd}[/tex]
From above, We can conclude that,
a = bk, b = ck, c = dk
a = dk³ , b = dk² , c = dk
By solving RHS :-
[tex]\sf{√(a - b - c)(b-c-d) }[/tex]
[tex]\sf{√(dk³ - dk² - dk) (dk² - dk - d) }[/tex]
[tex]\sf{√d(k³- k² - k) d(k² - k - 1)}[/tex]
[tex]\sf{d√(k³- k² - k) d(k² - k - 1)}[/tex]
[tex]\sf{d√k(k²- k - 1)(k² - k - 1)}[/tex]
[tex]\sf{d(k²- k - 1)√k ...eq(1)}[/tex]
By solving LHS :-
[tex]\sf{√ab - √bc - √cd}[/tex]
[tex]\sf{√dk³(dk²) - √dk²(dk)-√dk(d)}[/tex]
[tex]\sf{√d²k^5 - √ d²k³ - √d²k}[/tex]
[tex]\sf{dk²√k - dk√k - d√k}[/tex]
[tex]\sf{(dk² - dk - d)√k}[/tex]
[tex]\sf{d(k²- k - 1)√k...eq(2)}[/tex]
From eq(1) and eq(2)
[tex]\bold{\red{ LHS = RHS }}[/tex]
That is,
[tex]\sf{√(a-b-c)(b-c-d)=√ab-√bc-√cd}[/tex]
Yes, the RHS and the LHS are equal/
Given:
[tex]a/b= b/c = c/d[/tex]
We have to prove that √(a - b - c)(b-c-d) = √ab-√bc-√cd
Hence, after we expand the brackets and evaluate, we see that:
After the evaluation of the RHS and LHS, we can see that
RHS= LHS .
Read more about maths expressions here:
https://brainly.com/question/2164351